KNOWLEDGE THAT GOVERNS: A PROPOSAL FOR PROFESSIONAL DEVELOPMENT IN PUBLIC EXPENDITURE MANAGEMENT IN MARINGÁ (REMUNOM, 2026)
The professional qualification of public servants has been identified as a key factor in the efficiency of public management. However, diagnoses in the Municipality of Maringá revealed significant gaps in training actions aimed at budgetary and financial execution (Matara, 2025). This study aimed to propose a structured training plan for public servants who work directly or indirectly in the execution of public expenditure at the Municipality of Maringá, aiming to strengthen governance and institutional performance. Methodologically, the research is characterized as an exploratory case study with a qualitative approach and applied nature. The procedures included document analysis, application of questionnaires and interviews submitted to content analysis, culminating in the elaboration of a theoretical-practical model based on competency-based management and organizational learning. The results highlighted the need for a systemic approach, structuring the plan into four axes: technical, managerial, behavioral, and technological. The proposed plan is organized in a modular and three-year format, prioritizing active methodologies, such as practical workshops, which were preferred by 46% of the participants. It is concluded that the institutionalization of a permanent training policy, coupled with a shared governance structure and performance indicators, contributes to mitigating the risks of fiscal irregularities and consolidating ethical, transparent, and results-oriented public management. Thus, the study offers theoretical and practical support to public administration by demonstrating that a training model based on competency-based management enhances the efficiency of budget execution.